Effect of woven fabric on the shear capacity of short RC beams - Leung, Hau-yan (Journal of Civil Engineering and Management, 2003)
Recently, externally bonded fibre-reinforced polymer (FRP) composite plate has been used successfully to enhance the performance of reinforced concrete (RC) members. The non-corrosive property of FRP eliminates the corrosion problem, but the occurrence of premature cracking induced by the rigidity of FRP plates is still questionable. In current pilot study, woven fabric is adopted, in lieu of rigid plates, to provide the strengthening effect. An experimental programme was developed and a series of short RC model beams, including unloaded and preloaded specimens, were prepared and woven fabric straps were attached. Ultimate loading tests were earned out and the results were recorded. All specimens were specially designed to investigate the effect of woven fabric on the shear capacity of RC beams. The results demonstrate that the shear performance of both unpreloaded and preloaded RC members can be enhanced by more than 10 % if woven fabrics are employed. First Published Online: 26 Jul 2012